Synergy of Law and Education in Protecting Contract Workers in Indonesia - Arifuddin Muda Harahap; Safinatul Hasanah Harahap; Zulpahmi Lubis (Jurnal Cendikia ISNU SU, 2025)
This study examines the synergy between law and education in providing protection for contract workers in Indonesia. Contract workers are one group of workers who often face problems related to legal status, job insecurity, and limitations in obtaining normative rights as stipulated in labor regulations. Although Law Number 13 of 2003 concerning Manpower and its derivative regulations have provided a legal framework, implementation in the field often shows gaps that weaken the position of contract workers. Therefore, an interdisciplinary approach is needed that integrates legal and educational dimensions to provide more comprehensive protection. The research method used is normative legal research with a qualitative approach, through a review of labor laws, doctrines, and practices, and enriched with educational studies that emphasize the importance of legal literacy for workers. The results of the study indicate that legal protection for contract workers is not fully effective due to weak supervision, workers' low understanding of their rights, and the ongoing practice of contract abuse by employers. In this context, education plays a crucial role in increasing legal awareness among contract workers, through formal and informal education, as well as skills-based training in legal and employment law. The conclusion of this study confirms that the synergy between law and education is a relevant strategy for strengthening the protection of contract workers. The law provides a binding normative framework, while education fosters workers' awareness and empowerment in demanding their rights. Therefore, the combination of the two is expected to achieve social justice and improve the welfare of contract workers in Indonesia.